PERBEDAAN TINGKAT FEAR OF MISSING OUT PADA REMAJA DITINJAU DARI EMPAT TIPE KEPRIBADIAN EYSENCK - Elisabet Istharini; Rudangta Arianti (JURNAL PSIKOLOGI MALAHAYATI, 2022)
ABSTRACT :DIFFERENCES IN THE RATE OF FEAR OF MISSING OUT IN ADOLESCENTS REVIEW FROM FOUR TYPES OF PERSONALITY OF EYSENCK The desire of individuals to access social media is now inseparable from life today, without exception, teenagers. This is due to the increasing availability of internet-based communication media that is able to accelerate individuals in accessing information from within and outside the country. This increase in the use of social media has given rise to a new phenomenon called Fear of Missing Out (FoMO), which is a feeling of fear of losing precious moments so that you want to continue to connect with others through social media. This study aims to determine differences in the level of FoMO in adolescents in terms of 4 personality types involving 50 respondents with an age classification of 12-15 years and using active social media. The measuring instruments used in this research are Fear of Missing Out Scales (FoMOS) and Eysenck Personality Inventory (EPI). The data analysis technique used is the difference test using the Kruskal-Wallis test using the SPSS version 25.0 program by proving the results of the hypothesis obtained a significant level of p = .001 (<.05), that from these results it can be interpreted that there are differences in the level of FoMO in each each Personality Type. The implication of this study is that the differences in the level of FoMO among adolescents at SMP Kristen 1 Purwokerto are strongly influenced by the differences in the nature and characteristics of each personality type. This is expected to help the guidance and counseling teacher at SMP Kristen 1 Purwokerto in handling the problems experienced by students. Keyword: Fear of Missing Out, Personality Types. Keinginan individu untuk mengakses media sosial sekarang ini sudah tidak dapat dipisahkan dari kehidupan di masa kini, tanpa terkecuali remaja. Hal ini terjadi karena semakin bertambahnya ketersediaan media komunikasi berbasis internet yang mampu mempercepat individu dalam mengakses informasi dari dalam maupun luar negeri. Peningkatan penggunaan media sosial ini memunculkan fenomena baru yang disebut Fear of Missing Out (FoMO) yakni perasaan takut akan kehilangan momen berharga sehingga ingin terus terhubung dengan orang lain melalui media sosial. Penelitian ini bertujuan untuk mengetahui perbedaan tingkat FoMO pada remaja ditinjau dari 4 tipe kepribadian yang melibatkan 50 responden dengan klasifikasi usia 12-15 tahun dan menggunakan media sosial yang aktif. Alat ukur yang digunakan dalam penelitian ini adalah Fear of Missing Out Scales (FoMOS) dan Eysenck Personality Inventory (EPI). Teknik analisis data yang digunakan adalah uji perbedaan dengan menggunakan uji Kruskal-Wallis menggunakan program SPSS versi 25.0 dengan membuktikan hasil hipotesis diperoleh taraf signifikan sebesar p= .001 (<.05), bahwa dari hasil tersebut dapat diartikan terdapat perbedaan tingkat FoMO pada masing-masing Tipe Kepribadian. Implikasi dari penelitian ini adalah perbedaan tingkat FoMO pada remaja di SMP Kristen 1 Purwokerto sangat dipengaruhi oleh perbedaan sifat dan karakteristik yang dimiliki oleh masing-masing Tipe Kepribadian. Hal ini diharapkan dapat membantu Guru BK di SMP Kristen 1 Purwokerto dalam penanganan permasalahan yang dialami oleh siswa. Kata Kunci: Fear of Missing Out, Tipe Kepribadian